Mangroves as Protection from Storm Surges in a Changing Climate - Blankespoor, Brian; Dasgupta, Susmita; Lange, Glenn-Marie (World Bank, Washington, DC, 2016)
Adaptation to climate change includes addressing sea level rise and increased storm surges in many coastal areas. Mangroves can substantially reduce the vulnerability of the adjacent coastal land from inundation and erosion. However, climate change poses a large threat to mangroves. This paper quantifies the coastal protection provided by mangroves for 42 developing countries in the current climate, and a future climate change scenario with a one-meter sea level rise and 10 percent intensification of storms. The benefits of the coastal protection provided by mangroves are measured in terms of population and gross domestic product at a reduced risk from inundation; the loss of benefits under climate change is measured as the increased population and gross domestic product at risk. The findings demonstrate that although sea level rise and increased storm intensity would increase storm surge areas and the amounts of built resources at risk, the greatest impact is the expected loss of mangroves. Under current climate and mangrove coverage, 3.5 million people and roughly $400 million in gross domestic product of are at risk. In the future climate change scenario, the vulnerable population and gross domestic product at risk would increase by 103 and 233 percent, respectively. The greatest risk is in East Asia, especially in Indonesia, the Philippines, and Myanmar.